The complete chloroplast genome sequence of Pterocarpus macrocarpus - Zhang, Jinfeng (Mitochondrial DNA B Resour, 2020)
The first complete chloroplast genome (cpDNA) sequence of Pterocarpus macrocarpus was determined from Illumina HiSeq pair-end sequencing data in this study. The cpDNA is 154,734 bp in length, contains a large single copy region (LSC) of 88,418 bp and a small single copy region (SSC) of 18,790 bp, which were separated by a pair of inverted repeats (IR) regions of 23,763 bp. The genome contains 127 genes, including 84 protein-coding genes, 8 ribosomal RNA genes, and 35 transfer RNA genes. The overall GC content of the whole genome is 36.3%, and the corresponding values of the LSC, SSC, and IR regions are 33.8%, 30.2%, and 43.3%, respectively. Further phylogenomic analysis showed that P. macrocarpus in Pterocarpus genus clade in Papilionoideae subfamily.